Investigating Barriers That May Influence the Implementation and Use of E-HRM Tools in the Organization - Hamid Agahi; Sarist Gulthawatvichai (Advances in educational technologies and instructional design book series, 2021)
Human resource managers (HRMs) can use electronic-human resource management (E-HRMs) tools to improve human resources practices, including recruitment and selection of employees. Grounded in the theoretical framework of a unified theory of acceptance (UTAUT), this present qualitative case study investigated the potential barriers that influence the implementation and use of E-HRMs in Thailand's business sector. Human resource professionals from the business sector, including hotels in Thailand, were the study participants. Semi-structured interviews with open-ended questions were used as data collection instruments. Qualitative data collected was analyzed using thematic content analysis. The challenges impact the recruitment and selection process by making the employment process complex and poor selection of employees. HRMs should support E-HRMs as the advanced technologies to improve recruitment and selection of competent employees. In conclusion, E-HRMs are effective information systems that support electronic recruitment and selection of qualified employees.
Keywords: Employer Branding and e-HRM; Human Resource and Talent Management; AI and HR Technologies